Fluorescent Nitrones for the Study of ROS Formation with Subcellular Resolution - Hauck, Stefan; Lorat, Yvonne; Leinisch, Fabian; Kopp, Christian; Abrossinow, Jessica; Trommer, Wolfgang E. (IntechOpen, 2012)
None